2002
DOI: 10.2337/diacare.25.8.1405
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of Type 1-Fimbriated Escherichia coli to Uroepithelial Cells

Abstract: OBJECTIVE -Women with diabetes have bacteriuria more often than women without diabetes. Because Escherichia coli adhere better to vaginal cells of nondiabetic patients with recurrent urinary tract infections (UTIs) than to those obtained from healthy control subjects, it was hypothesized that E. coli adhere more to the uroepithelial cells of diabetic women, either because of substances excreted in the urine (e.g., albumin, glucose, and Tamm Horsfall protein) or because of a difference in the uroepithelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(91 citation statements)
references
References 33 publications
3
84
0
4
Order By: Relevance
“…Glucose is detectable in airway secretions and may support the [24]. Escherichia coli adhesion to uroepithelial cells is increased in diabetic patients [25], and elevated urinary glucose levels support the growth of bacteria [26]. Lack of metabolic control, as measured by glycated haemoglobin, is a risk factor for bacteriuria [27].…”
Section: Discussionmentioning
confidence: 99%
“…Glucose is detectable in airway secretions and may support the [24]. Escherichia coli adhesion to uroepithelial cells is increased in diabetic patients [25], and elevated urinary glucose levels support the growth of bacteria [26]. Lack of metabolic control, as measured by glycated haemoglobin, is a risk factor for bacteriuria [27].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the E coli with type 1 fimbriae adhere to the uroepithelial cells of diabetic women are twice as well as to the urothelium of nondiabetic controls. 36,37 Although in this study we did not flush the bladder after concluding a cystoscopy with D10, one could consider attempting to flush the D10 to decrease this adherence. Further study would be necessary to support this practice.…”
Section: Commentmentioning
confidence: 97%
“…Uropathogenic E. coli expressing type 1 fimbriae but no P fimbriae were twice as adherent to cells from women with diabetes as compared with cells collected from the women without diabetes (109). No differences in adherence were seen using the E. coli strain expressing no known uropathogenic adhesins or for the isolate expressing only P fimbriae (109). These data suggest that uroepithelial cells from women with diabetes may have intrinsic differences in nature and/or amount and/or affinity of binding receptors for type 1 fimbriae, such as uroplakins.…”
Section: Female Sexual Dysfunctionmentioning
confidence: 97%
“…Another recent study examined the ability of three representative clinical isolates of uropathogenic E. coli to adhere to uroepithelial cells collected from urine of women with and without diabetes (109). Uropathogenic E. coli expressing type 1 fimbriae but no P fimbriae were twice as adherent to cells from women with diabetes as compared with cells collected from the women without diabetes (109).…”
Section: Female Sexual Dysfunctionmentioning
confidence: 99%